Kepadatan Bakteri Biofertilizer Cair Air Kelapa Menggunakan Bakteri Pelarut Fosfat (Bacillus spp.) Asal Tanah Gambut Kalimantan Barat: Density of Liquid Biofertilizer Coconut Water Bacteria Using Phosphate Solubilizing Bacteria (Bacillus spp.) from West Kalimantan Peat Soil - Sari, Lala; Rahmawati; Khotimah, Siti; Mukarlina (Universitas Negeri Semarang, 2025)
Biofertilizer is an environmentally friendly fertilizer, has a long release time so it can be absorbed by plants long enough, and has enzymatic activities such as binding nitrogen and dissolving phosphate. Phosphate solubilizing bacteria (BPF) can dissolve phosphate that was previously unavailable to become available. This research aims to further examine the potential of BPF isolates from Kalimantan as a liquid biofertilizer agent using coconut water as a medium. The research was conducted for 3 months, from June to August 2023 at the Microbiology Laboratory, Biology Department, Faculty of Mathematics and Natural Science Tanjungpura University, Pontianak. This research used a Completely Randomized Design (CRD) with 8 treatments and 3 replications using the Total Plate Count method. The results of the study showed that the highest treatment is a treatment of A4 on day 6 with an average density of 9,4x108 CFU/mL. The BPF which has the highest potential as a biofertilizer is found in treatment A4, the combination bacterial isolates of Bacillus sp1 and Bacillus sp2, supported by the high population treatment of A4 during each storage. Liquid biofertilizers have many advantages compared to solid biofertilizers, including having a higher number of microbial cells, longer shelf life, greater protection against the environment and better effectiveness in the field. This study can provide information on the density of liquid biofertilizer bacteria using environmentally friendly coconut water media for the community by using phosphate-solubilizing bacteria (Bacillus spp.) from West Kalimantan peat soil.